Microscopic computation in human brain evolution. - Wallace, Ron (Behavioral Science, 1995)
The writer discusses the evolution of microscopic computation from theoretical and empirical standpoints. A microscopic neurological model stressing the computational power of excited atoms within the neuronal membrane is advanced as an alternative to classical connectionist approaches. The evolution of the system and its relation to local optima or very good solutions are examined in the context of social and mapping requirements of a competitive hunting and scavenging niche. The relationship of microscopic computation to the nature of consciousness is discussed, and possible mathematical models as a basis for simulation studies are briefly considered.